Forensic DNA databases in European countries: is size linked to performance? - Santos, Filipe (2013)
The political and financial investments in the implementation of forensic DNA databases and the ethical issues related to their use and expansion justify inquiries into their performance and general utility. The main function of a forensic DNA database is to produce matches between individuals and crime scene stains, which requires a constant input of individual profiles and crime scene stains. This is conditioned, among other factors, by the legislation, namely the criteria for inclusion of profiles and the periods of time and conditions for their retention and/or deletion. This article aims to provide an overview of the different legislative models for DNA databasing in Europe and ponder if wider inclusion criteria – and, consequently, database size – translates into more matches between profiles of crime scene stains and included individuals (performance ratio). The legislation governing forensic DNA databases in 22 countries in the European Union was analysed in order to propose a typology of two major groups of legislative criteria for inclusion/retention of profiles that can be classified as having either expansive effects or restrictive effects. We argue that expansive criteria for inclusion and retention of profiles do not necessarily translate into significant gains in output performance.